The role of podcasts in agricultural extension: Enhancing farmer-to-farmer learning - Cinthia, F C; Hariraj, N; Karthikeyan, C; Thamaraiselvi, S P; Manivasakan, S (Plant Science Today, 2025)
The rise of digital communication tools has opened new avenues for agricultural extension, with podcasts emerging as a powerful medium for farmer-to-farmer learning. This study explores the effectiveness of podcast-based agricultural education in enhancing knowledge dissemination among farmers in the Coimbatore region. Adopting an action research design, podcast interviews were created with 30 farmers, including both pesticide-using and innovative practitioners. These podcasts were then disseminated to another group of 30 purposively selected farmers to evaluate awareness and attitudinal changes. The study employed ranking techniques like Garrett ranking and word cloud analysis using NVivo software to interpret the responses. The results revealed that podcasts significantly contributed to creating awareness, improving knowledge, shaping positive attitudes and encouraging symbolic and actual adoption of agricultural innovations. Respondents found the content relatable, easy to understand and accessible, highlighting the value of localized and experience-based communication. Despite these positive outcomes, the study identifies research gaps, such as limited understanding of long-term behavioural changes and the need for scalability across diverse farming communities. The findings suggest that podcasts can be a cost-effective and impactful tool in agricultural extension when integrated with participatory approaches and supported by ICT infrastructure. Future research should focus on measuring the economic benefits, enhancing content delivery in multiple languages and fostering community-driven content creation to sustain interest and impact.